PID H? FUZZY AND FUZZY-REFERENCE CONTROL SYSTEM FOR SPEED OF SRM MOTOR IN ELECTRIC VEHICLES - Rizalul Wahid, Muhammad
The SRM motor is the solution to the problems associated with driving motors on electric vehicles that have complex construction. The SRM motor has a very simple construction consisting only of rotors and stators without permanent magnets inside. The application of the controller on the SRM motor needs to be done in order to obtain a system response that is more stable and has a high performance against changes in the rate of input. In this study a Fuzzy reference logic control algorithm was developed to compensate the errors coming from the system response due to changes in reference values. The PID H? controller is also applied to make the system more stable and can reach the reference value given which is make errors smaller. Additional controller Fuzzy logic is used to smooth the system response by rejecting the ripple. The PID H? controller which is equipped with Fuzzy logic and coupled with the Fuzzy reference controller provides the best performance that is able to make the system more stable and has the smallest RMSE value of 2,633. The value of rising time is also the shortest when changing the reference value from 30 kmph to 40 kmph which is 1,201 seconds. The same result was also obtained in the load system given, the PID H? controller which is equipped with Fuzzy logic and coupled with the Fuzzy reference logic controller give the best results with an RMSE value of 3,536 with a rise time of 3,855 seconds.